2016
DOI: 10.1542/peds.2015-0117
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Perinatal Mortality in Nepal Using Helping Babies Breathe

Abstract: BACKGROUND AND OBJECTIVE: Newborns are at the highest risk of dying around the time of birth, due to intrapartum-related complications. Our study’s objective was to improve adherence to the Helping Babies Breathe (HBB) neonatal resuscitation protocol and reduce perinatal mortality by using a quality improvement cycle (QIC) in a tertiary hospital in Nepal. METHODS: The HBB QIC was implemented through a multifaceted approach, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 21 publications
5
91
1
1
Order By: Relevance
“…However, when analysing both periods together and adjusting for the HBB training, results were in line with the baseline, suggesting that the intervention did not change the resuscitation practice for LBW compared to NBW infants in this setting. The finding of higher odds of ventilation of LBW infants supports the previous finding of a reduced rate of intrapartum stillbirths after training in HBB, as almost half of those stillbirths were LBW infants [8]. The data for gestational age in this study were not complete, but the cases with available information on gestational age confirmed the global estimates of the relatively high proportion of moderately premature infants [25,26].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, when analysing both periods together and adjusting for the HBB training, results were in line with the baseline, suggesting that the intervention did not change the resuscitation practice for LBW compared to NBW infants in this setting. The finding of higher odds of ventilation of LBW infants supports the previous finding of a reduced rate of intrapartum stillbirths after training in HBB, as almost half of those stillbirths were LBW infants [8]. The data for gestational age in this study were not complete, but the cases with available information on gestational age confirmed the global estimates of the relatively high proportion of moderately premature infants [25,26].…”
Section: Discussionsupporting
confidence: 86%
“…This study focused on evaluating differences in steps of neonatal resuscitation between LBW and NBW infants; therefore it is difficult to compare with previous observational studies of HBB interventions. However, HBB training in Nepal and India resulted in an increased rate of ventilation whereas the same intervention in Tanzania demonstrated a lower rate of ventilation after training [68]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the skills acquired through initial training diminish over time, our findings indicate the skills diminish less quickly when supplemented by a single two-day refresher course provided one year after the initial training. It is also likely that the midwives’ self-reflection after each delivery as a result of maintaining delivery logs also contributed to the delay in skills decay following the refresher when compared to the initial course, which has also been suggested by a study in Nepal [14]. …”
Section: Discussionmentioning
confidence: 90%